2012
DOI: 10.2196/jmir.1847
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Online Community Needs Assessment for Psychoeducational Interventions Among Partners of Hereditary Breast Cancer Previvors and Survivors

Abstract: BackgroundSpouses and partners (“partners”) of women at-risk for (“previvors”) and surviving with hereditary breast/ovarian cancer are a primary source of support within their families. Yet, little is known about partners’ needs for psychoeducational intervention to enhance their cancer risk knowledge, coping, and support role functioning.ObjectiveTo determine the type and range of need for psychoeducational intervention among partners of hereditary breast cancer previving and surviving women, and to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Partners of women undergoing genetic testing for BRCA1/2 may face an especially challenging dilemma: they are a primary source of support for women who undergo genetic testing, yet they may also experience distress themselves and have limited access to supportive resources (Tercyak et al, 2012; Mireskandari et al, 2007; Patenaude et al, 2006; Sherman, Kasparian, & Mireskandri, 2010). Indeed, emerging data suggest that partners of women who are at risk for hereditary breast/ovarian cancer perceive a need for supportive interventions to help them cope with their partner’s risk of cancer and to better prepare them to provide support during the genetic counseling and testing process (Tercyak et al, 2012). Through a dyadic perspective, our results provide empirical support for the need to develop targeted interventions to help parents engage in shared decision making surrounding the communication of BRCA1/2 test results to their children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partners of women undergoing genetic testing for BRCA1/2 may face an especially challenging dilemma: they are a primary source of support for women who undergo genetic testing, yet they may also experience distress themselves and have limited access to supportive resources (Tercyak et al, 2012; Mireskandari et al, 2007; Patenaude et al, 2006; Sherman, Kasparian, & Mireskandri, 2010). Indeed, emerging data suggest that partners of women who are at risk for hereditary breast/ovarian cancer perceive a need for supportive interventions to help them cope with their partner’s risk of cancer and to better prepare them to provide support during the genetic counseling and testing process (Tercyak et al, 2012). Through a dyadic perspective, our results provide empirical support for the need to develop targeted interventions to help parents engage in shared decision making surrounding the communication of BRCA1/2 test results to their children.…”
Section: Discussionmentioning
confidence: 99%
“…Women who undergo BRCA1/2 genetic counseling and testing express a high level of need for supportive resources offered through diverse delivery methods (e.g., in-person, print materials) (Sharff et al, 2012; Tercyak et al, 2007). Recent data show that partners express a similarly high level of need for supportive resources delivered through both electronic (e.g., internet) and more traditional media (e.g., print materials) (Sharff et al, 2012; Tercyak et al, 2012). While the clinical context of genetic counseling may be an opportunity to engage partners who attend counseling sessions with tested mothers, couples-oriented interventions that can be offered as adjuncts to clinical care may be optimal, as a minority of partners attend genetic counseling sessions with tested women (DeMarco et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies most often focused on breast cancer (n = 22; 31.9%),8,10,12,13,16,17,22,25,26,2830,35,4143,45,58,60,66,74,75 and prostate cancer (n = 4; 5.8%). 36,56,67,76 Other cancers mentioned were osteosarcoma, 73 rhabdomyosarcoma, 55 testicular, 11 skin, 23 cervical, 37,53,59,65 ovarian, 21, lung, 34 and colorectal.…”
Section: Resultsmentioning
confidence: 99%
“…Other descriptive studies (n = 12; 17.4%; Table 2) used surveys, 11,23,24,28,40,43,46,59,60,63,65,74 in-depth interviews, 47 focus groups, 48 social network analyses, 20,68 a mix of measurement techniques, 8,9,13,22,30,39 Web metrics, 72,73 and frequencies 62 to describe how users employed social media to obtain and receive cancer information. It is important to note that only 1 of these studies reviewed the accuracy of information posted on a social media site (YouTube); it reported that roughly 75% of all videos had either fair or poor information about prostate cancer screening.…”
Section: Resultsmentioning
confidence: 99%